Поширення та регресивні зміни ареалу сосни кедрової європейської (Pinus cembra L.) в Українських Карпатах - Sirenko, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
This article is presents the detailed cartographic materials on distribution of a european cedar pine (Pinus cembra L.). The list of new and disappered localities is given. Changes of woody stands with participation of the species for the last 25 years is given.